Sistem Pakar dalam Membandingkan Metode Forward Chaining dengan Certainty Factor untuk Mengidentifikasi Jenis Kulit Wajah - Nadya Alinda Rahmi; Gunadi Widi Nurcahyo (Jurnal Sistim Informasi dan Teknologi, 2021)
Skin is one piece of the body that has adaptable properties to shield the human body from natural effects. A great many people need facial skin that is tight and liberated from skin illnesses, particularly skin inflammation inclined skin. Next, everybody ought to do facial consideration and utilize a few fixings that are appropriate for facial skin, there are five kinds of ordinary skin, sleek skin, dry skin, blend skin and touchy skin. To inspect the kind of facial skin by contrasting the Forward Chaining and Certainty Factor procedures. This assessment utilizes 30 information acquired from interviews with subject matter experts. There are a few signs acquired from different issues distinguished on facial skin which are utilized as indication data for facial skin types constrained by subject matter experts. This data is utilized to check the sort of facial skin dependent on guidelines and data from a trained professional. The preliminary advances taken are to look at the Forward Chaining and Certainty Factor strategies. The outcomes acquired subsequent to testing and assessment of the Forward Chaining and Certainty Factor strategies were 83.33% and the discoveries expressed that the customer had a commonplace skin type. The test outcomes can be seen from the two strategies that test unequivocal facial skin types, then, at that point the principle system utilized not set in stone to help dermatologists in analyzing facial skin types.